2021
DOI: 10.34172/ijhpm.2021.09
|View full text |Cite
|
Sign up to set email alerts
|

Economic Costs of Providing District- and Regional-Level Surgeries in Tanzania

Abstract: Background: Access to surgical care is poor in Tanzania. The country is at the implementation stage of its first National Surgical, Obstetric, and Anesthesia Plan (NSOAP; 2018-2025) aiming to scale up surgery. This study aimed to calculate the costs of providing surgical care at the district and regional hospitals. Methods: Two district hospitals (DHs) and the regional referral hospital (RH) in Arusha region were selected. All the staff, buildings, equipment, and medical and non-medical supplies deployed in ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…This will ensure timely access to surgical care, reduce the number of preventable referrals and overcrowding at higher-level hospitals [ 30 ]. Unit costs and the relative shares of capital costs are generally lower at primary-level hospital [ 31 ]. Effective treatment depends on all steps of a healthcare system working harmoniously, from timely seeking and reaching healthcare, appropriate triage for surgery or referral, to proper transportation for care in an adequately resourced facility for better outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…This will ensure timely access to surgical care, reduce the number of preventable referrals and overcrowding at higher-level hospitals [ 30 ]. Unit costs and the relative shares of capital costs are generally lower at primary-level hospital [ 31 ]. Effective treatment depends on all steps of a healthcare system working harmoniously, from timely seeking and reaching healthcare, appropriate triage for surgery or referral, to proper transportation for care in an adequately resourced facility for better outcomes [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Instead, there may be a waste of resources unless, as in the case of Malawi, such additional resources consist of surgically active personnel. An earlier study in Tanzania [ 37 ] also demonstrated that clinicians’ surgical skills and staff skills-mix are major factors that determine efficiency of resource use and economies of scale. However improvements in surgical skills will not result in increased volume and efficiency if other rate-limiting steps are not removed simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…We performed primary and secondary cost analyses using gross costing approaches ( Hellebo et al. , 2021 ; Ifeanyichi et al. , 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we performed a secondary analysis of the centre-specific costs of AMR by multiplying the estimated provider cost per bed day by the estimated LOS due to AMR for each cost centre/department. The analysis was, in essence, a check of the robustness of the crude estimates in the primary analysis ( Ifeanyichi et al. , 2022 ).…”
Section: Methodsmentioning
confidence: 99%